The philosophy of protecting people working on civil-law basis. A voice in the discussion during the 1st Nationwide Scientific Conference from the series ‘Non-standard employment relations’ entitled ”Applying civil-law contracts in the light of the labour law regulations and social insurance. Łódź and Poznań beginning of the discussion...” - Musiała, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The study pertains to the common misconception of an issue that is fundamental for the labour law, namely the problem of the legal grounds for employment. It is about what actually determines the choice of these grounds, and more precisely whether it is ‘free will’ of parties that is ultimately decisive in this respect. The questions are as follows: is it erroneous that the legislators have chosen the direction of equating the legal grounds for employment in the sphere of labour law and civil law? Next, if it is the case, what should certain ‘planning’ of the legal grounds for work provision look like, and what determines the legislators’ decision about this planning, or maybe it is this ‘free will’ of the parties that is solely decisive here? Finding the answer to the above questions is of primary importance in order to counter the wave of criticism to the proposals included in the draft code on individual labour law prepared by the Codification Committee in the years 2016–2018.